76.0k views
4 votes
G(t) = -9t – 4
g(
) = 23

2 Answers

3 votes

Answer:-23

Explanation:

I got it right

User Onessa
by
6.0k points
5 votes

Answer:

e the equation as

(

f

+

g

2

)

h

=

A

.

(

f

+

g

2

)

h

=

A

Combine

f

+

g

2

and

h

.

(

f

+

g

)

h

2

=

A

Divide each term by

h

and simplify.

Tap for more steps...

f

+

g

2

=

A

h

Multiply both sides of the equation by

2

.

2

f

+

g

2

=

2

A

h

Cancel the common factor of

2

.

Tap for more steps...

f

+

g

=

2

A

h

Subtract

f

from both sides of the equation.

g

=

2

A

h

f

Explanation:

User Toshiaki
by
5.9k points